Direct room-temperature synthesis of methyl-functionalized Ti-MCM-41 nanoparticles and their catalytic performance in epoxidation - Lin, Kaifeng; Pescarmona, Paolo P.; Houthoofd, Kristof; Liang, Duoduo; Van Tendeloo, Gustaaf; Jacobs, Pierre A. (Journal of catalysis, 2009)
Methyl-functionalized Ti-MCM-41 nanoparticles with a size of 80 to 160 nm (Me-Ti-MCM-41 NP) were directly prepared via a dilute solution route by the co-condensation of tetraethoxysilane and methylalkoxysilanes in sodium hydroxide medium at room temperature. The characterization results showed the existence of ordered hexagonal mesoporous structure and tetrahedral Ti species in the nanoparticles. In the epoxidation of cyclohexene with tert-butyl hydroperoxide and aqueous H 2O 2, Me-Ti-MCM-41 NP samples displayed higher turnover frequencies (TOFs) for cyclohexene and initial reaction rates compared to Ti-MCM-41 and methyl-functionalized Ti-MCM-41 with normal particle size and to non-functionalized Ti-MCM-41 nanoparticles. Simultaneously, a higher selectivity for cyclohexene epoxide was observed in the case of aqueous H 2O 2, suggesting that the hydrolysis of cyclohexene epoxide with water is reduced on Me-Ti-MCM-41 NP samples. The improved catalytic behavior of Me-Ti-MCM-41 NP is discussed both in terms of the nanosize and methylation of the surface of the catalyst particles. The regeneration of Me-Ti-MCM-41 NP with tert-butyl hydroperoxide solution was evaluated via washing and calcination approaches. Methyl-functionalized Ti-MCM-41 nanoparticles display improved catalytic performance in the epoxidation of cyclohexene.